Korkeasti koulutettujen henkilökohtaiset urasaavutukset ja niiden yhteys työn merkityksellisyyteen : kestävien työurien näkökulma - Keränen, Milja; Latvakoski, Inka (2024)
Personal career achievements are defined as career-related achievements that an individual perceives as personally significant. The aim of this study was to gain information on the personal career achievements of Finnish highly educated professionals and explore how these achievements relate to career sustainability. We investigated what kinds of personal career achievements participants describe, whether background factors are related to these achievements, and how career achievements are rated in terms of importance and career advancement as well as satisfaction and stress experienced. We also examined the connection between personal career achievements and job meaningfulness. The final sample (N = 579), collected through a questionnaire, consisted of professors, scientists, economists, academic engineers, and Executive MBA management training participants.